A STUDY OF THE IMPACT OF CO-CURRICULAR ACTIVITIES ON THE SOCIAL SKILLS AND EMOTIONAL MATURITY OF STUDENTS STUDYING IN NON-GOVERNMENT SCHOOLS - Jha, Pragya; Dewangan, Savita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary objective of this study is to evaluate the impact of co-curricular activities on the social skills and emotional maturity of Grade 10 students in non-government schools in Durg district, Chhattisgarh. For the study, 295 students (143 male, 152 female) were selected from 10 non-government schools through simple random sampling. Social skills were measured using the Social Skills Rating Scale (SSR) developed by Vishal Sood, Aarti Anand, and Suresh Kumar (2012), and emotional maturity was measured using the Emotional Maturity Scale (EMS) developed by Tara Sabapathy (2017). The data were analyzed using t-tests and correlation analysis. The results revealed significant differences in social skills (t=2.799, p=0.005) and emotional maturity (t=2.501, p=0.013) between male and female students in non-government schools. Female students performed better than male students in both areas. Furthermore, a moderate to high positive correlation (r=0.458, p<0.01) was found between social skills and emotional maturity. The study concludes that the impact of co-curricular activities in non-government schools clearly highlights gender-based developmental disparities. These findings are important for policymakers and education administrators to ensure gender equality in non-government schools.